Flanimales pop-up - Gervais, Ricky; Steen, Rob; Fernandez, Laura (Edebé, 2010)
A field guide to a bizarre group of creatures called Flanimals showcases their many colorful varieties and their odd behavior, disgusting diet, and strange way of interacting. - A pop-up field guide to a bizarre group of creatures called Flanimals showcases their many colorful varieties and their odd behaviors, disgusting diets, and strange ways of interacting